2013
DOI: 10.1016/j.talanta.2013.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Sol–gel thin-film based mesoporous silica and carbon nanotubes for the determination of dopamine, uric acid and paracetamol in urine

Abstract: This work describes the preparation, characterization and application of a hybrid material composed of disordered mesoporous silica (SiO2) modified with multiwalled carbon nanotubes (MWCNTs), obtained by the sol-gel process using HF as the catalyst. This hybrid material was characterized by N2 adsorption-desorption isotherms, X-ray powder diffraction (XRD), scanning electron microscopy (SEM), high resolution transmission microscopy (HR-TEM), Raman spectroscopy and X-ray photoelectron spectroscopy (XPS). This n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 68 publications
3
46
1
2
Order By: Relevance
“…At last, FWHM and SoS values used in curve fittings should always be reported (see [69] for a good example) but this is rarely done. Canevari et al [104] and Fernandes et al [108] are appreciable examples of correctly reporting the results of XPS curve fittings.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…At last, FWHM and SoS values used in curve fittings should always be reported (see [69] for a good example) but this is rarely done. Canevari et al [104] and Fernandes et al [108] are appreciable examples of correctly reporting the results of XPS curve fittings.…”
Section: Discussionmentioning
confidence: 97%
“…Canevari et al described the preparation of a hybrid material composed of disordered mesoporous silica modified with multiwalled carbon nanotubes [104]. The material was characterized by N2 adsorption-desorption isotherms, XRD, FESEM, HRTEM, Raman and XPS techniques.…”
Section: Botelho Do Rego Et Al Performed a Cv/xps Investigation Of Tmentioning
confidence: 99%
“…The hybrid material was prepared according to the following procedure [1]: TEOS (0.009 mol) was mixed with ethanol in the proportion 1/1 (v/v) and the solution was left stirring for 10 min. Then, 180 mg of graphene oxide was added together with 0.8 mL of H 2 O and the suspension was kept stirring for more 10 min.…”
Section: Synthesis Of Hybrid Materials Sio 2 /Gomentioning
confidence: 99%
“…The synergism that occurs between different components of the hybrid material improves its properties in comparison to each isolated one and, thus, increases its potential as well as its applications in several fields. In this way, hybrid organic-inorganic materials based on silica-containing carbon allotropes have long been used as a basis to support the development of electrochemical sensors, due to their high chemical stability, robustness, functional groups presence and excellent electrochemical properties [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…According to Table S1, it is clear that the modified electrode developed in this study has a lower detection limit than some of the reported modified electrodes, 11,1416 while the linear dynamic range of the present study is also better than the values reported in most earlier studies. 2,13 The fabrication reproducibility for three MWCNTs/PLL/ GCE was investigated by comparing the oxidation peak current of 20.0¯M DA and PA. The relative standard deviation (RSD%) values in five replicate measurements using three different electrodes were 3.4% (for DA) and 3.8% (for PA).…”
mentioning
confidence: 99%